Entering the Dragon’s Den: Contemporary Risks and Opportunities of China’s Belt and Road Initiative in Africa (The Strategic Review for Southern Africa, 2022)
This article attempts to identify the opportunities and risks associated with China’s Belt and Road Initiative (BRI) in Africa. Given the global scope and depth of the BRI, it is of considerable importance to understand how this initiative applies to developing economies in the African context. The article provides a brief historical context of the BRI, followed by a short theoretical framework, specifically in the scholarly field of International Relations. The article then expounds on the opportunities the BRI could create for Africa, such as improving infrastructure, assisting in African industrialisation and economic advancement, as well as introducing beneficial diplomatic initiatives. The article also examines the strategic risks associated with the BRI, such as unsustainable debt concerns, concerns regarding the effect of an increasing trade deficit on domestic markets, as well as risks pertaining to large-scale infrastructure development.
Keywords: Belt and Road Initiative; China in Africa; Health Silk Road; Digital Silk Road; Debt-trap Diplomacy; Political Economy